Effects of sulphur on the yield, yield component characters and oil content of oilseed rape - Rameeh Valiollah; Niakan Maryam; Mohammadi Mohammad H. (Journal of Agricultural Sciences (Belgrade), 2021)
The effects of four sulphur levels: S0, S1, S2 and S3, including 0, 12, 24 and 36 kg S ha-1, respectively, along with 115 kg N ha-1 were studied on yield-related traits of oilseed rape (Brassica napus L.). The significant variance of treatments was determined for plant height, yield component characters, seed yield and oil content. The sulphur application significantly increased most of the traits compared to the S0 level. The S3 (36 kg S ha-1) treatment led to the highest mean value of plant height (132 cm) which was classified with S2 (24 kg S ha-1) in the same statistical group. Sulphur had an increasing effect on pods per plant, and it ranged from 92 to 196 for S0 and S3 applications, respectively. S0 and S1 with 92 and 121 pods per plant were grouped in the same statistical group. In addition, S2, and S3 with 165 and 196 pods per plant showed no significant statistical difference. The sulphur application significantly increased seed yield compared to control (S0 level), and it ranged from 2744 to 3215 kg ha-1 in S0 and S3, respectively. The average oil contents of 45.69, 46.96, 47.46 and 49.53 % were detected for 0, 12, 24 and 36 kg S ha-1, respectively.